Papular acantholytic dyskeratosis localized to the perineal and perianal area in a young male - Shyam B Verma (Wolters Kluwer Medknow Publications, 2013)
A case of Papular acantholytic dermatosis restricted to the perianal area is being reported in a 26 year old male without involvement of the genitalia, groin and upper thighs for the first time in English literature. The patient presented with long standing grayish white confluent papules with eroded areas in the perianal region which were asymptomatic for a long time before the area got macerated. He did not respond to many weeks of topical steroids but is now showing improvement with topical tacrolimus ointment 0.1% applied twice daily. This entity appears to be very uncommon and also underreported. It is also suggested that this entity be included in the long list of non venereal anogenital lesions as it may mimic perianal warts or molluscum contagiosum.